The Effect of Information Technology Integration on Student Competence in ICT Learning at Nurul Ulum Vocational High School - Tri Wahyuni; Siti Seituni; Dyan Yuliana (FKIP - Universitas Riau, 2026)
The integration of Information and Communication Technology (ICT) has become a critical component in vocational education, particularly in enhancing student competencies. This study aims to examine the relationship between ICT integration and student competency at SMK Nurul Ulum. A quantitative correlational design was employed, involving 22 students selected through total sampling. Data was collected using a structured questionnaire and analyzed using Pearson correlation and simple linear regression techniques. The findings indicated a positive correlation between ICT integration and student competency (r = 0.341); however, this relationship was not statistically significant (p = 0.121). The coefficient of determination (R² = 0.116) showed that ICT integration accounted for 11.6% of the variance in student competency, while the remaining 88.4% was influenced by other factors. The study concludes that ICT integration demonstrates a positive tendency toward improving student competencies, yet its impact is limited and requires reinforcement from pedagogical strategies, teacher digital literacy, and a supportive learning environment.